How can we capture the subject’s perspective? An evidence-based approach for the social scientist - Lahlou, Saadi (Social Science Information, 2011)
This paper addresses the methodological gap that impedes the collection of empirical data on subjective experience. It describes a new family of methods for social science research (Subjective Evidence-Based Ethnography: SEBE). The methods are based on: first-person audio-visual recording with a miniature video-camera worn at eye-level (‘subcam’); confronting subjects with these first-person recordings to collect their subjective experience; formulating the findings and discussing the final interpretation with the subjects. These procedures enable subjects to reconstruct and describe their psychological state at the moment of action, especially their goals, by reviewing films of their own activity recorded from their own perspective with subcams. These films provide situated records of actual activity in natural environments, without the need of an external observer. This approach, by providing both detailed records of actual activity and evidence-based accounts of the subject’s own mental processes, supports grounded progress in ethnography, psychology, ergonomics, sociology and the social sciences in general. There are also applications for training and cross-cultural contacts. The techniques are described in sufficient detail for the reader to make use of them. Examples of applications are provided and limitations are discussed.